Modernizing Composition : Sinhala Song, Poetry, and Politics in Twentieth-Century Sri Lanka - Field, Garrett M., 1981- (Book collections on Project MUSE., 2017)
"The study of South Asian music falls under the purview of ethnomusicology, whereas that of South Asian literature falls under South Asian studies. As a consequence of this academic separation, scholars rarely take notice of connections between South Asian song and poetry. Modernizing Composition overcomes this disciplinary fragmentation by examining the history of Sinhala-language song and poetry in twentieth-century Sri Lanka. Garrett Field describes how songwriters and poets modernized song and poetry in response to colonial and postcolonial formations. The story of this modernization is significant in that it shifts focus from India's relationship to the West to little-studied connections between Sri Lanka and North India."--Provided by publisher.